Lurbinectedin in Refractory Diffuse Malignant Peritoneal Mesothelioma: Report of Two Cases - Gros, Louis; Szturz, Petr; Diciolla, Antonella; Kirchner, Volker; Peters, Solange; Schaefer, Niklaus; Hubner, Martin; Digklia, Antonia (Frontiers in Oncology, 2021)
Mesothelioma is a malignancy of serosal membranes. Parietal pleura is the most common site, with peritoneum being the second most frequent location. Malignant peritoneal mesothelioma (MPM) is a rare and aggressive disease. The prognosis is often very poor with median overall survival ranging from 6 to 18 months in patients who are not candidates for cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) due to non-resectable disease or comorbid conditions. For patients with resectable disease, CRS and HIPEC have become the standard of care. However, for patients with unresectable malignant mesothelioma there is unfortunately no effective systemic treatment beyond the first line. Based on the results of a recent phase II trial, lurbinectedin has clinical activity and acceptable toxicity in the second- and third-line treatment of malignant pleural mesothelioma. However, until present, no data have been available for patients with MPM and for patients who become refractory after multiple treatment lines. We report on two patients with metastatic MPM who achieved durable disease control of 10+ and 8 months with lurbinectedin in the fourth and fifth treatment line, respectively.